500 nations [videorecording (DVD)] - Leustig, Jack; Leustig, Jack; Leustig, Jack; Grossman, Roberta; Harrison, Gregory, 1950- (Warner Bros. Entertainment Inc., 2019)
"The amazing story of America's original inhabitants has been crystallized into a powerful epic event on four discs. The insight that actor, filmmaker and series host, executive producer Kevin Costner brought to Dances with Wolves serves as a springboard to this thrilling chronicle filmed at actual locations, from the jungles of Central America to the Canadian Arctic. A cast of star voices and state-of-the-art computer re-creations brings this rich, untold story to vivid life." -- Container.